2021
DOI: 10.1016/j.btre.2021.e00611
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of enzymatic hydrolysis of red tilapia scales (Oreochromis sp.) to obtain bioactive peptides

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 63 publications
3
10
0
Order By: Relevance
“…In another study on red tilapia ( Oreochromis sp.) proteins, the processing conditions of 58.5 °C, pH 8.1, alcalase 4.42 g/L along with a substrate concentration of 45 g/L obtained the highest activity of antioxidant peptides on free radicals scavenging . The two-stage enzymatic hydrolysis is also known as gastrointestinal digestion, which involves sequential in vitro simulated digestion by pepsin and trypsin .…”
Section: Extraction Of Bps From Seafoodmentioning
confidence: 99%
“…In another study on red tilapia ( Oreochromis sp.) proteins, the processing conditions of 58.5 °C, pH 8.1, alcalase 4.42 g/L along with a substrate concentration of 45 g/L obtained the highest activity of antioxidant peptides on free radicals scavenging . The two-stage enzymatic hydrolysis is also known as gastrointestinal digestion, which involves sequential in vitro simulated digestion by pepsin and trypsin .…”
Section: Extraction Of Bps From Seafoodmentioning
confidence: 99%
“…Fish proteins contain between 16 and 18 amino acids, which have an excellent balance, usually 8 essential and 8 non-essential. This makes this type of protein very widely used for animal feed, although they are also used for fertilizer production, silage and in recent decades, bioactive peptide production [30,40]. Table 3 shows the aminograms of different residues of several fish species, some raw and others that have undergone hydrolysis processes [14], atomization drying [40] and membrane fractionation [11].…”
Section: Bromatological Characteristics Of the Main Fish-farmed By-pr...mentioning
confidence: 99%
“…This procedure has advantages over chemical hydrolysis as they have high selectivity and low contamination. It is a specific process that is carried out under moderate pH and temperature conditions, which makes it easy to control [30]. The product obtained is called protein hydrolyzate and it consists of peptides generally between 2 and 20 amino acids [48].…”
Section: Enzymatic Hydrolysis Of Proteinmentioning
confidence: 99%
See 1 more Smart Citation
“…Because a protein is the precursor of bioactive peptides, substances with a high protein content are abundant sources of bioactive peptides. , It is found that the AMPs and antioxidant peptides identified at present mainly come from foods (such as milk and cheese), animals (such as porcine bone and duck plasma), plants (such as bean and cottonseed), and bacteria (such as Lactobacillus and Bacillus amyloliquefaciens) (Table ). In recent years, to save energy or reduce production costs, some industrial and agricultural byproducts are also used to produce AMPs and antioxidant peptides, such as waste coffee grounds, baijiu vinasse, and scales and epidermal mucus of fish. , In addition, AMPs and antioxidant peptides with expected biological activity and low toxicity can be synthesized through chemical synthesis and gene expression to overcome the limitations of natural AMPs and antioxidant peptides …”
Section: Bioactive Peptides For Food Preservationmentioning
confidence: 99%